2012
DOI: 10.1590/s1516-14392012005000014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of calcium carbonate obtained from oyster and mussel shells and incorporation in polypropylene

Abstract: There is a high content of calcium carbonate in mussel and oyster shells, which can be used in the formulation of medicine, in construction or as filler in polymer materials. This work has as its main objective to obtain calcium carbonate from mussel and oyster shells and used as filler in polypropylene compared their properties with polypropylene and commercial calcium carbonate composites. The shellfish was milling and heated at 500 °C for 2 hours. The powder obtained from shellfish were characterized by sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(95 citation statements)
references
References 13 publications
3
81
1
10
Order By: Relevance
“…The optimum curing time is close to 20-25 min since the storage modulus tends to a constant value of 3.6 MPa as observed in influence the oxidation of the polymeric matrix appear in concentrations below to 0.5 wt. % reducing the risk of this kind of oxidation [22].…”
Section: Figurementioning
confidence: 99%
“…The optimum curing time is close to 20-25 min since the storage modulus tends to a constant value of 3.6 MPa as observed in influence the oxidation of the polymeric matrix appear in concentrations below to 0.5 wt. % reducing the risk of this kind of oxidation [22].…”
Section: Figurementioning
confidence: 99%
“…36 SEM images of neat epoxy showed brittle type of fracture while CB/EP and HB/ EP composites showed smooth fracture surfaces. Previous studies [13][14][15]20 have reported the use of organic compounds to improve the interaction between CaCO 3 and matrix. Cuttlebone particles having organic compounds on the surface by nature induced good interaction between filler and composites.…”
Section: Morphology Study Of Compositesmentioning
confidence: 99%
“…Penerbitan yang telah dilakukan dijadikan sebagai pendekatan referensi dan acuan dalam peningkatan kualitas hasil pemijahan hingga 656 http://itk.fpik.ipb.ac.id/ej_itkt72 pembesaran di laut. Pertumbuhan cangkang kerang dan pembentukan butiran adalah hasil biomineralisasi dari lapisan cairan nacre yang mengandung kalsium karbonat (CaCO 3 ) (Naganuma et al, 2014;Caiping et al, 2005;Hamester et al, 2012). Dikemukakan pula bahwa persentasi kandungan kalsium karbonat dalam cangkang kerang sebesar 95% sementara sisanya adalah kandungan bahan organik yang lain (Hamester et al, 2012;Feng et al, 2009) Proses pembentukan cangkang larva kerang mutiara sangat ditentukan oleh ketersedian kalsium karbonat yang diproduksi oleh enzim dalam mencerna protein.…”
Section: Pendahuluanunclassified
“…Pertumbuhan cangkang kerang dan pembentukan butiran adalah hasil biomineralisasi dari lapisan cairan nacre yang mengandung kalsium karbonat (CaCO 3 ) (Naganuma et al, 2014;Caiping et al, 2005;Hamester et al, 2012). Dikemukakan pula bahwa persentasi kandungan kalsium karbonat dalam cangkang kerang sebesar 95% sementara sisanya adalah kandungan bahan organik yang lain (Hamester et al, 2012;Feng et al, 2009) Proses pembentukan cangkang larva kerang mutiara sangat ditentukan oleh ketersedian kalsium karbonat yang diproduksi oleh enzim dalam mencerna protein. Sebagaimana dikemukakan oleh Naganuma et al (2014) bahwa kegagalan pembentukan cangkang kerang mabe (Pteria penguin) pada fase D-veliger sangat ditentukan oleh ketersedian komponen protein yang digunakan untuk proses metabolisme enzim dalam pembentukan cairan nacre yang menghasilkan elemen kristal kalsium karbonat (CaCO 3 ).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation